Brain Plasticity and Learning Implications for Educational Practice - Hawkins, Jennifer Anne.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This book synthesizes the latest findings on neuroplasticity and learning, drawing on rich phenomenological research carried out with teachers, psychologists, parents and students from around the world to examine the implications for current teaching and for the advancement of learning methods. Building on the author$1 (Bs previous work in this area, the volume considers in depth the function of feelings and emotions in neuroplastic cognition, and provides an analysis of curriculum debates and assessment systems in the light of neuroplasticity. The final chapters explore the implications of brain plasticity outside of structured learning environments and in society at large. The book will appeal to students and scholars of psychology and education, as well as to educational psychologists, coaches, teachers and educational leaders. Jennifer Anne Hawkins is an independent researcher and author. Dr. Hawkins draws on extensive previous experience as primary and secondary teacher, teacher trainer and educational evaluator. Her previous works include: Feelings and Emotion-based Learning; A New Theory (2017).s
Chapter 1: The Discovery of Neuroplasticity -- Chapter 2: The Importance of Feelings and Emotions -- Chapter 3: The Plastic Brain and Its Educational Development -- Chapter 4: Curriculum and Assessment Systems for Teaching -- Chapter 5: Inclusion, Exclusion, and Special Educational Needs -- Chapter 6: Education and Mental Well-being -- Chapter 7: Knowledge, World Outlooks and Influences -- Chapter 8: Political and Economic Implications for Society -- Chapter 9: A summary of how a better understanding of brain plasticity might help us improve society.
Keywords: Educational psychology; Education; Personal coaching; Teachers$1 (BTraining of.s; Educational Psychology; Education Science; Coaching; Teaching and Teacher Education